2020
DOI: 10.1002/ijfe.2362
|View full text |Cite
|
Sign up to set email alerts
|

The financial requirements of tech startups over its lifecycle in Bangalore: An analysis of why and how do they differ?

Abstract: It is widely recognized by researchers, practitioners and policy makers that for a tech startup adequate financial capital is an essential resource in order to emerge, survive and grow over its lifecycle. However, there is a lack of understanding on what are the various needs for financing, what factors drive these needs and how do they vary over a startup's lifecycle. This study makes a key contribution to the literature by investigating the financial requirements for a tech startup and their determinants bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…Research funds are grants given to entities to conduct scientific research and is usually given through a competitive process (Neema & Chandrashekar, 2021). Singh and Subrahmanya (2020) concluded that financial funding is important for the survival, and growth of startups. While funding categories can be classified broadly as public and private, Doblinger et al (2019) argued that the funding of universities by the government are in two forms, which includes—provision of funds for R&D to reduce the cost of research, and the implementation of policies to improve the incentives researchers can get.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Research funds are grants given to entities to conduct scientific research and is usually given through a competitive process (Neema & Chandrashekar, 2021). Singh and Subrahmanya (2020) concluded that financial funding is important for the survival, and growth of startups. While funding categories can be classified broadly as public and private, Doblinger et al (2019) argued that the funding of universities by the government are in two forms, which includes—provision of funds for R&D to reduce the cost of research, and the implementation of policies to improve the incentives researchers can get.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…The works identified in this review point to a direct influence of R&D on startups' competitiveness (Franca Vargas et al, 2016;Jones & Crick, 2000;Rydehell et al, 2019;Xiao & Zhao, 2017). Singh & Bala Subrahmanya (2020) argue that a high-tech startup to achieve increasing competitiveness must innovate in new products or technologies throughout its life cycle, investing in R&D continuously. Besides, the resources that startups have similarly influence their competitiveness.…”
Section: Fpv 1: Organizationalmentioning
confidence: 99%
“…From an organizational point of view, the aforementioned factors guide the startup's internal efforts and should be closely managed to aim the organizational competitiveness. There is a prevalence of studies related to five factors within this FPV, namely: Innovative Profile, R&D, Resources, Absorptive Capacity, and Value Creation (Asadinasab et al, 2013;Asmoro & Nugroho, 2018;Caseiro & Coelho, 2019;Dezi et al, 2009;Franca Vargas et al, 2016;Gwebu et al, 2019;Jones & Crick, 2000;Marullo et al, 2018); Petti & Zhang, 2013;Rydehell et al, 2019;Samaeemofrad & Van Den Herik, 2018a,b;Singh & Bala Subrahmanya, 2020;Skawińska & Zalewski, 2020;Tangkesalu & Suseno, 2018;Teixeira & Ferreira, 2019;Utomo & Simatupang, 2019;Xiao & Zhao, 2017). This suggests that, theoretically, these are the most important factors within the organizational aspect.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Franca Vargas et al (2016), Jones and Crick (2000), Rydehell et al (2018Rydehell et al ( , 2019, Singh and Bala Subrahmanya (2020) Grilli and Murtinu (2012), Jones and Crick (2000), Kozubikova et al (2019), Luo et al (2021), Xiao and Zhao (2017) Alliance formation Asadinasab et al (2013), Baum and Silverman (2004), Caseiro and Coelho (2019), Jones and Crick (2000), Marullo et al (2018) Table 1. CSFs related to startups' competitiveness…”
Section: Csf Referencesmentioning
confidence: 99%